PENERAPAN KOLABORASI MODEL PEMBELAJARAN JIGSAW DENGAN MIND MAPPING SEBAGAI UPAYA PENINGKATAN PRESTASI BELAJAR SISWA - Susilowati, Enik (Jurnal Analisis Pendidikan Sosial, 2024)
This study aims to determine the increase in student achievement through the collaboration of the Jigsaw Learning Model with Mind Mapping in social studies subjects. This type of research is Classroom Action Research which consists of 2 cycles, each cycle is carried out in 2 meetings. Stages of Classroom Action Research consist of four steps, namely action planning, action implementation, observation and reflection on the results of the action. The subjects of this study were students of class VIIIA social studies subjects at MTsN 2 Mojokerto, totaling 31 students. The research approach used was qualitative and the data were analyzed descriptively. In this study, the data collection method was through tests, observations, interviews, and documentation. Based on the results of the study, it is known that the increase in student achievement is indicated by an increase in the average value of student achievement in both the pre-test and post-test. It is known that the average test score of students in the first cycle before the application of collaborative Jigsaw learning with Mind Mapping was 50 with the highest score of 65 and none of the 31 students had completed learning (Score ? 75). After implementing the Jigsaw Learning Collaboration Model with Mind Mapping, the average score of students increased to 70.65 with the highest score of 85 and the number of students who completed learning (Score ? 75) as many as 13 students. While in the second cycle the average test score of students before the application of Jigsaw learning collaboration with Mind Mapping was 75 with the highest score of 80 and the number of students who completed learning (Score ? 75) were 21 students. After applying Jigsaw learning collaboration with Mind Mapping, the average score of students increased to 90 with the highest score of 100 and the number of students who finished learning (Score ? 75) was 31 students or the total number of students who attended had completed learning.